IMPlementing split Regimen OVEr Single dose using a Plan-Do-Study-Act approach (IMPROVES study) - Vanella, Giuseppe; Hassan, Cesare; De Bellis, Mario; Giardini, Maxemiliano; Grasso, Enrico; Laterza, Francesco; Tarantino, Ottaviano; Di Giulio, Emilio (Endoscopy International Open, 2019)
Background and aims A split-dose regimen for colonoscopy is recommended by international guidelines, but its adoption is still suboptimal. Our aim was to assess whether a Plan-Do-Study-Act approach (PDSA), a scientific method promoting quality improvement, would be able to improve adherence to a split-dose regimen, and to identify factors influencing its adoption.Methods This study consisted of three phases: Cycle 1: a cross-sectional assessment of split-dose adherence in consecutive outpatients/inpatients undergoing colonoscopies in 74 Italian centers; Educational intervention: regional meetings with literature review, analysis of Cycle 1 data, and discussion on corrective measures; local diffusion of educational material and tools for improvement; Cycle 2: reassessment of split-dose adherence after spontaneous local interventions. Demographic, clinical, and procedural variables were systematically collected. Multivariate logistic regression was used to identify predictors of split-dose adoption.Results In total, 8213 patients (mean age = 60.29 years (SD = 13.58), men = 54 %, outpatients = 88.4 %) were enrolled between 2013 and 2016 (Cycle 1 = 4189 patients and Cycle 2 = 4024 patients). Split-dose adoption rose from 29.1 % in Cycle 1 to 51.1 % in Cycle 2 (P < 0.0001), and being enrolled in Cycle 2 independently predicted split-dose adherence (OR = 2.9; 95 %CI 2.6 – 3.3). The adoption improved in all time slots, including colonoscopies scheduled before 0930. The main corrective measures were: rescheduling of colonoscopies after 0930 (between 0930 and 1130: OR = 2.6; 95 %CI 2.3 – 3.1; after 1130: OR = 7; 95 %CI 5.9 – 8.4); the cleansing regimen communicated by the Endoscopy unit (via form: OR = 1.6; 95 %CI 1.3 – 1.9; via visit: OR = 2.1; 95 %CI 1.7 – 2.5); a decrease in the use of deep sedation (OR = 2; 95 %CI 1.7 – 2.5).Conclusions An educational intervention with observation-driven corrections through a PDSA approach was able to substantially increase the adoption of a split-dose regimen.